2017
DOI: 10.15252/embj.201695748
|View full text |Cite
|
Sign up to set email alerts
|

A microRNA‐129‐5p/Rbfox crosstalk coordinates homeostatic downscaling of excitatory synapses

Abstract: Synaptic downscaling is a homeostatic mechanism that allows neurons to reduce firing rates during chronically elevated network activity. Although synaptic downscaling is important in neural circuit development and epilepsy, the underlying mechanisms are poorly described. We performed small RNA profiling in picrotoxin (PTX)-treated hippocampal neurons, a model of synaptic downscaling. Thereby, we identified eight microRNAs (miRNAs) that were increased in response to PTX, including miR-129-5p, whose inhibition b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 64 publications
9
91
1
Order By: Relevance
“…Notably, BIC increased spine head diameter in neurons expressing the E17R and T19K mutants by ~9% and ~3%, respectively, augmenting the actual difference in spine size changes between WT and mutants although none of these effects reached statistical significance. This observation is analogous to findings by Rajman et al (), that is, treatments that prevented down scaling BIC increased rather than decreased spine size (see Discussion). Remarkably, we found that BIC robustly increased spine length by 20–30% for WT as well as the PSD‐95 mutants.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Notably, BIC increased spine head diameter in neurons expressing the E17R and T19K mutants by ~9% and ~3%, respectively, augmenting the actual difference in spine size changes between WT and mutants although none of these effects reached statistical significance. This observation is analogous to findings by Rajman et al (), that is, treatments that prevented down scaling BIC increased rather than decreased spine size (see Discussion). Remarkably, we found that BIC robustly increased spine length by 20–30% for WT as well as the PSD‐95 mutants.…”
Section: Resultssupporting
confidence: 90%
“…One possibility is that differences in the culturing conditions are responsible for this difference. However, similar to the increase in spine size we observed in neurons expressing the Ca 2+ /CaM‐binding‐deficient PSD‐95 mutants (Fig EV4A), the work by Rajman et al () also found such an increase when blocking scaling down. In detail, chronic picrotoxin treatment, which, like BIC, increases network activity by inhibiting GABA A receptors, resulted in a modest spine enlargement when miR129, which is required for down scaling, was down regulated with anti‐miR129 plasmid.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Finally, although miRNA-based therapeutics in the brain are still in their infancy, in large part due to the difficulty of delivering miRNAtargeting oligonucleotides into the brain, some advances have been made. A notable example is that of epilepsy, for which injection of several miRNA antagomirs has proven to be beneficial for the reduction of seizures and associated neurodegeneration in the hippocampus (Gross et al, 2016;Jimenez-Mateos et al, 2012;Rajman et al, 2017). In addition, the virus-directed expression of miR-223 has been shown to be neuroprotective following transient global ischemia and excitotoxic injury (Harraz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…About 60% of all human proteins are estimated to be directly regulated by miRNAs [7]. Recent research suggests that miRNAs play key roles in the pathogenesis of a variety of neurological disorders, including epilepsy [8-11]. Moreover, some miRNAs have been found differentially expressed in the brain under pathological conditions and might therefore represent both therapeutic targets and diagnostic or prognostic biomarkers for epilepsy [12-15].…”
Section: Introductionmentioning
confidence: 99%